2017
DOI: 10.1038/srep44294
|View full text |Cite
|
Sign up to set email alerts
|

Revealing new insights into different phosphorus-starving responses between two maize (Zea mays) inbred lines by transcriptomic and proteomic studies

Abstract: Phosphorus (P) is an essential plant nutrient, and deficiency of P is one of the most important factors restricting maize yield. Therefore, it is necessary to develop a more efficient program of P fertilization and breeding crop varieties with enhanced Pi uptake and use efficiency, which required understanding how plants respond to Pi starvation. To understand how maize plants adapt to P-deficiency stress, we screened 116 inbred lines in the field and identified two lines, DSY2 and DSY79 that were extreme low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…Due to the promising plant growth-promoting effects of PGPM combinations in the previous experiment (Figure 3A), a range of consortium products were tested as microbial inoculants: Combifector-A (see Section 4.2) Combifector-B ( Trichoderma harzianum OMG16 + Bacillus amyloliquefaciens FZB42 + Zn/Mn), Bacillus amyloliquefaciens FZB42 + humic acids, and Bacillus amyloliquefaciens FZB42 + seaweed extract. Since many studies have demonstrated the importance of early root development as a critical trait determining yield formation of maize particularly with respect to P acquisition [33,34,35], special emphasis was placed on the selection of PSMs with additional root growth-promoting potential (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the promising plant growth-promoting effects of PGPM combinations in the previous experiment (Figure 3A), a range of consortium products were tested as microbial inoculants: Combifector-A (see Section 4.2) Combifector-B ( Trichoderma harzianum OMG16 + Bacillus amyloliquefaciens FZB42 + Zn/Mn), Bacillus amyloliquefaciens FZB42 + humic acids, and Bacillus amyloliquefaciens FZB42 + seaweed extract. Since many studies have demonstrated the importance of early root development as a critical trait determining yield formation of maize particularly with respect to P acquisition [33,34,35], special emphasis was placed on the selection of PSMs with additional root growth-promoting potential (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…Above- and belowground dry matter production were statistically not different between cultivars without P ( Figure 5B ), and both cultivars had an intermediate PAE in the genotype screen, which might be the reason for similar behavior in root phosphatase activity. For maize, it was shown that low-P tolerant genotypes showed higher (Gaume et al, 2001; Jiang et al, 2017) or earlier (Du et al, 2016) root acid phosphatase activity than sensitive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Several time-course transcriptome (Woo et al, 2012 ; Secco et al, 2013 ; Ren et al, 2018 ), proteome (Iglesias et al, 2013 ; Jiang et al, 2017 ), and metabolome (Alexova et al, 2017 ) studies on Pi depletion and resupply are available. However, PTM studies that focus on temporal development of the Pi-stress response are limited to phosphorylation (Gregory et al, 2009 ; Yang J. et al, 2019 ), ubiquitination (Iglesias et al, 2013 ; Ye et al, 2018 ; Pan et al, 2019 ), and sumoylation (Kant et al, 2011 ; Feng et al, 2017 ; Datta et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%